2019
DOI: 10.14414/jebav.v22i2.1694
|View full text |Cite
|
Sign up to set email alerts
|

The effect of non-financial performance on financial performance moderated by information disclosure

Abstract: This research aimed to test the effect of non-financial performance on financial performance moderated by information disclosure. A tool used to measure performance values in a comprehensive, coherent, measurable, and balanced was balanced scorecard (Kaplan and Norton, 1992). This research method was quantitative with survey technique. The research result showed that non-financial performance measures were consumer, learning and growth affect financial performance, but the research result showed that the perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…by the company during the period is certain; ROE, ROE is the ratio of net income after tax to common stock equity, evaluating the ROR on investment from ordinary shareholders; sales growth for a certain period; ROI or ROR or the ROR on investment, i.e. the amount of return received divided by the amount invested (Refmasari and Supriyono, 2019). A firm's business objective is not only meeting the shareholders' wishes but also securing supply chain partners and society at large.…”
Section: Interactions Of Sustainability Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…by the company during the period is certain; ROE, ROE is the ratio of net income after tax to common stock equity, evaluating the ROR on investment from ordinary shareholders; sales growth for a certain period; ROI or ROR or the ROR on investment, i.e. the amount of return received divided by the amount invested (Refmasari and Supriyono, 2019). A firm's business objective is not only meeting the shareholders' wishes but also securing supply chain partners and society at large.…”
Section: Interactions Of Sustainability Practicesmentioning
confidence: 99%
“…Škrinjar et al (2008) found several indicators that explain the measure of financial performance as follows: ROA, ROA is the ratio between net incomes before available tax divided by total assets owned by the company; the amount of profit/profit growth obtained by the company during the period is certain; ROE, ROE is the ratio of net income after tax to common stock equity, evaluating the ROR on investment from ordinary shareholders; sales growth for a certain period; ROI or ROR or the ROR on investment, i.e. the amount of return received divided by the amount invested (Refmasari and Supriyono, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%